Pengaruh Kompetensi Aparatur Pengelola Dana Desa, Komitmen Organisasi Dan Kejelasan Sasaran Anggaran Terhadap Akuntabilitas Pengelolaan Dana Desa Sekecamatan Banjarangkan - Wati, Ni Luh Aprilia; Hutnaleontina, Putu Nuniek (UNHI Press, 2025)
The purpose of this study was to determine whether or not the accountability of village fund management in Banjarangkan District was affected by managers' competence, organizational commitment, and the clarity of budget targets. A total of 185 local officials from Banjarangkan District participated in the research. The Village Head, Village Secretary, Three Kaur, and Three Heads of Section were therefore chosen as samples for this research. The study's information came from the responses to questionnaires, which were analyzed using a PLS regression model. The study's findings suggest that accountability for managing village funds is influenced by the quality of the apparatus used to do so. Management accountability and village funds are unaffected by organizational dedication. The transparency and accountability of village finances depend on a well-defined budget.